2022
DOI: 10.1126/sciadv.abm8804
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for C-type inactivation in a Shaker family voltage-gated K + channel

Abstract: C-type inactivation is a process by which ion flux through a voltage-gated K + (K v ) channel is regulated at the selectivity filter. While prior studies have indicated that C-type inactivation involves structural changes at the selectivity filter, the nature of the changes has not been resolved. Here, we report the crystal structure of the K v 1.2 channel in a C-type inactivated state. The structure shows that C-type inactivation involves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 60 publications
6
33
0
Order By: Relevance
“…Our previous work on the Kv1.2 channel had predicted aspartate flipping, SF dilation and loss of K + ions from S0-S2, also using the CHARMM force field [31], before recent cryoEM structures of stably-inactivated Shaker W434F, Kv1.2 W362F and Kv1.3 channels became available ( Fig. 6 C-F ) [27,29,30]. In MthK, previous MD simulations done with the CHARMM force field (and reduced interaction strength between K + ions and carbonyl oxygens) revealed that K + ions from sites S1, S2, and S3 need to unbind before the SF collapse, which was then structurally similar to the one seen in KcsA, having a constriction at the level of the ‘first’ glycine (G61), V60 and G61 carbonyl flipping and increased number of water molecules behind the SF [32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work on the Kv1.2 channel had predicted aspartate flipping, SF dilation and loss of K + ions from S0-S2, also using the CHARMM force field [31], before recent cryoEM structures of stably-inactivated Shaker W434F, Kv1.2 W362F and Kv1.3 channels became available ( Fig. 6 C-F ) [27,29,30]. In MthK, previous MD simulations done with the CHARMM force field (and reduced interaction strength between K + ions and carbonyl oxygens) revealed that K + ions from sites S1, S2, and S3 need to unbind before the SF collapse, which was then structurally similar to the one seen in KcsA, having a constriction at the level of the ‘first’ glycine (G61), V60 and G61 carbonyl flipping and increased number of water molecules behind the SF [32].…”
Section: Resultsmentioning
confidence: 99%
“…Structures of KcsA, stably-inactivated mutants of voltage-gated K + channels ( Shaker W434F and Kv1.2 W362F) and WT Kv1.3 channels revealed that C-type inactivation-related conformational changes at the SF can follow at least two distinct paths ( Fig. 6 ) [27][28][29][30] : in KcsA the SF pinches (constricts) at the level of the 'first' glycine (G77, corresponding to G61 in MthK), which is accompanied by flipping of valine (V76 in KcsA, corresponding to V60 in MthK) carbonyl away from the SF axis. The SF also loses two K + ions during inactivation, and has remaining ions bound at S1 and S4, whereas S3 is occupied by a water molecule, which presumably enhances the valine flipping.…”
Section: Longer In Silico Electrophysiology Simulationsmentioning
confidence: 99%
“…Sodium conduction across the C-type inactivated state has been experimentally observed in hERG and also in the voltage-gated Shaker channel . Furthermore, in recent experimental structures of a fast inactivating mutant of Shaker, both by cryo-EM and by X-ray crystallography, the SF appeared with binding sites S3 and S4 perfectly intact but with S1 and S2 sites enlarged compared to the canonical structure (Figure b). Thus, inactivation of Shaker seems to imply a widening of the extracellular portion of the SF rather than a constriction of its central region, as observed in the KcsA channel.…”
Section: Discussionmentioning
confidence: 99%
“…al may largely plastic the cellular ion homeostasis. The mechanism of C-type inactivation 2426 and N-type inactivation 27,28 has some examples. However, the delayed rectifier activation coupled with the Cole-Moore effects remains elusive 3 .…”
Section: Discussionmentioning
confidence: 99%
“…al may largely plastic the cellular ion homeostasis. The mechanism of C-type inactivation [24][25][26] and N-type inactivation 27,28 has some examples.…”
Section: Mechanism Of Delayed Rectifier and Cole-moore Effectsmentioning
confidence: 99%